1993
DOI: 10.1093/ajcn/57.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue fatty acids as biomarkers of dietary exposure in Danish men and women

Abstract: Adipose tissue fatty acids, it has been proposed, reflect dietary intake. Using data from a validation study preceding a prospective study on diet, cancer, and health in Denmark, we were able to compare fatty acid profiles in adipose tissue biopsies from 86 individuals (23 men and 63 women) aged 40-64 y and dietary intake of fatty acids (as percentage of total fat) assessed by two 7-d weighed-diet records or by a semi-quantitative food frequency questionnaire. Correlation coefficients (Pearson r) between fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
4
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 9 publications
8
52
4
5
Order By: Relevance
“…One such study compared fatty acid composition of adipose tissue to dietary intake (as a percentage of total fat) as estimated from an FFQ for 86 adults and reported correlations of 0.42 for DHA and 0.55 for EPA (Tjonneland et al, 1993). Similar to our study, they found that nonmarine omega-3 fatty acids and omega-6 fatty acids were less correlated.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…One such study compared fatty acid composition of adipose tissue to dietary intake (as a percentage of total fat) as estimated from an FFQ for 86 adults and reported correlations of 0.42 for DHA and 0.55 for EPA (Tjonneland et al, 1993). Similar to our study, they found that nonmarine omega-3 fatty acids and omega-6 fatty acids were less correlated.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies in adults have compared fatty acid intake as determined by dietary survey with that of a biomarker, such as fatty acid content of the erythrocyte membrane (Feunekes et al, 1993;Romon et al, 1995;Parra et al, 2002), of serum phospholipids (Kobayashi et al, 2003), of platelet phospholipids (Li et al, 2001) or of adipose tissue (Hunter et al, 1992;Feunekes et al, 1993;Tjonneland et al, 1993;Lemaitre et al, 1998;Knutsen et al, 2003;Cantwell et al, 2005). In general, significant correlations were found between PUFA intake and these biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The intake of very-longchain n-3 fatty acids was higher than found among Danes (Bang et al, 1980;Tjùnneland et al, 1993), Swedes (Nydahl et al, 1996) and US health professionals (Ascherio et al, 1995), and lower than among Icelanders (Steingrimsdottir et al, 1995). The intake of EPA in the present study (0.34 gad) was higher than earlier reported from inland districts of Northern Norway (0.25 gad), but lower than reported (0.9 gad) from coastal districts (Simonsen et al, 1988).…”
Section: Discussionmentioning
confidence: 88%
“…The intake of very-long-chain n-3 fatty acids is described in clinical trials (Bùnaa et al, 1990;Sùyland et al, 1994;Brude et al, 1997), selected groups (Bang et al, 1980;Tjùnneland et al, 1993;Nydahl et al, 1996;Hjartaker et al, 1997) and prospective studies (Morris et al, 1995;Ascherio et al, 1995;Dolecek, 1992;Pietinen et al, 1997), but little information is available about the intake of very-long-chain n-3 fatty acids in random samples of populations (Steingrimsdottir et al, 1995). We therefore assessed the intake and sources of very-long-chain n-3 fatty acids and related the intake to socio-demographic and life-style variables in a national dietary survey.…”
Section: Introductionmentioning
confidence: 99%
“…The fatty acid composition of adipose tissue is widely held to be a useful`independent' marker of long-term dietary fat intake (Field & Clandinin, 1984;Van Staveren et al, 1986;Hunter et al, 1992;Tjonneland et al, 1993). The direct relationship between adipose tissue fatty acids and the composition of dietary fat has been long established in animals (Tove & Smith, 1959) and man (Shepherd et al, 1980).…”
Section: Introductionmentioning
confidence: 99%